2015
DOI: 10.1371/journal.pone.0144410
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Predictors and Outcomes of Delayed Breast Reconstruction in Mastectomized Women in Mainland China: An Observational Study

Abstract: BackgroundThe aim of the present study was to evaluate potential psychosocial factors that impact Chinese female breast cancer patients to select breast reconstruction (BR), and potential connection of psychosocial outcomes with their satisfaction with BR.MethodsA total of 264 female breast cancer patients with mastectomy were recruited from 2012 to 2014. All patients were informed with BR options at their first visit. Personal and medical profiles were collected. Body image, self-esteem, depression and anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
1
8
0
1
Order By: Relevance
“…The various parameters associated with HRQoL such as depression, pain, self-esteem, and body image showed a statistically significant improvement in women who underwent breast reconstruction. 12 Thus, the observation of this study correlates with the observations reported in the Middle East that breast reconstruction is one of the effective ways of coping in post-mastectomy patients. However, a multitude of factors could be responsible for lack of coping in women who undergo mastectomy and do not opt for breast reconstruction.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The various parameters associated with HRQoL such as depression, pain, self-esteem, and body image showed a statistically significant improvement in women who underwent breast reconstruction. 12 Thus, the observation of this study correlates with the observations reported in the Middle East that breast reconstruction is one of the effective ways of coping in post-mastectomy patients. However, a multitude of factors could be responsible for lack of coping in women who undergo mastectomy and do not opt for breast reconstruction.…”
Section: Resultssupporting
confidence: 88%
“…33 In the present review, breast reconstruction postmastectomy was observed as a significant coping strategy to improve the overall quality of life post-mastectomy. 12,[18][19][20][21] Although there is no consensus reached on this, it is still widely considered a safer option. A systematic review conducted on the same observed the reconstruction rates are highly variable in women.…”
Section: Discussionmentioning
confidence: 99%
“…An indication for this explanation was also provided by Yang et al who reported no differences in satisfaction between the various types two years after the reconstruction and noted that complications played a significant role [36]. A finding that was not replicated by Zhang et al who reported a non-significant relation between complications and satisfaction [37]. During the entire BR course DIEP flap BR patients reported lower anxiety distress scores than implant BR patients, this could be caused by the longer time between mastectomy and BR [38].…”
Section: Discussionmentioning
confidence: 99%
“…Um grupo de apoio a mulheres mastectomizadas tem como objetivos o apoio social e o compartilhamento de informações, oferecendo um local propício ao diálogo reflexivo sobre o câncer de mama e a mastectomia, trocando experiências e dúvidas sobre o enfretamento da situação que cada uma está vivenciando, conseguindo favorecer a confiança e melhor retorno e adaptação ao convívio social (12) . Ademais, melhora a sexualidade e a autoestima (7) , que são muito afetadas após a realização da cirurgia (13) . O grupo de apoio promove, ainda, esperança para as mulheres (14) .…”
Section: Revista Enfermagem Atual In Derme -Especial 2019; 87unclassified